2021
DOI: 10.2174/1381612827666210719104950
|View full text |Cite
|
Sign up to set email alerts
|

Female Sexual Dysfunction: A Problem Hidden in the Shadows

Abstract: Background: Female sexual dysfunction (FSD) has mainly been underdiagnosed and undertreated due to the lack of concrete definitions, validated assessment methods, and efficient treatments. However, during the last few decades, there has been significant progress in the clinical management and research of FSD. Objective: The purpose of this review is to describe the pathophysiology of FSD, report the prevalence of the disease in the setting of cardiovascular (CV) risk factors and disease, and review curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…Because there are no clear definitions, reliable evaluation techniques, or effective treatments for FSD, the condition has been significantly underdiagnosed and undertreated [21] . FSD is a complicated disorder influenced by biologic, psychiatric, and social variables.…”
Section: Discussionmentioning
confidence: 99%
“…Because there are no clear definitions, reliable evaluation techniques, or effective treatments for FSD, the condition has been significantly underdiagnosed and undertreated [21] . FSD is a complicated disorder influenced by biologic, psychiatric, and social variables.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of diabetes on sexual well-being can 8,17,21 However, according to the available research, it has been observed that women tend to exhibit greater hesitancy in addressing matters related to sexual health, while healthcare providers may display a decreased inclination to engage in discussions on such concerns with their female patients. 13,21,22 The potential causes of this phenomenon can be attributed to variations in gender-based communication patterns, societal expectations around gender roles, and the presence of unconscious prejudices within therapeutic settings. 22,23 Research has indicated that women may encounter heightened levels of stigmatization about disclosing personal health matters, particularly those about sexual health.…”
Section: Dovepressmentioning
confidence: 99%
“…13,21,22 The potential causes of this phenomenon can be attributed to variations in gender-based communication patterns, societal expectations around gender roles, and the presence of unconscious prejudices within therapeutic settings. 22,23 Research has indicated that women may encounter heightened levels of stigmatization about disclosing personal health matters, particularly those about sexual health. 22,24 In certain societal contexts, there exists an expectation for women to maintain a state of silence regarding matters about sexuality.…”
Section: Dovepressmentioning
confidence: 99%
See 2 more Smart Citations